PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN RETURN ON ASSET TERHADAP NILAI PERUSAHAAN PROPERTY, TBK. - Novi Indriana; Muninghar Muninghar (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to determine and analyze the effect of the current ratio, debt to equity ratio and return on assets on firm value. This type of research is quantitative research using comparative causal method. The population of Property, Tbk companies is 63 Property companies with the period 2019-2021. The sampling technique used in this study is purposive sampling with the number of samples obtained based on predetermined criteria, namely as many as 16 Property, Tbk companies for the period 2019-2021. Data analysis was performed using statistics with SPSS version 25. Based on the results of data analysis using t test, it is known that partially current ratio, debt to equity ratio and return on assets have a significant effect on firm value. Meanwhile, based on the results of data analysis using F test, it is known that simultaneous the current ratio, debt to equity ratio and return on assets have a significant effect on firm value